Avicenna's Logic of Ethics - Tayyebeh Ahmadi (MAQOLAT: Journal of Islamic Studies, 2024)
This article deals with the logic of ethical propositions, i.e. the reason for the integrity of ethical rules from Avicenna's point of view. It begins with the consideration of Ara-e Mahmoudeh (accepted norms), the philosopher's first and most famous keyword, which describes the essence of ethics and explains the reason for its observance in a person's life. Considering Avicenna's logic of ethics and through critical analysis, two new conclusions can be stated: 1) Avicenna's ethics is compatible with contemporary evolutionary explanations of ethics due to its non-platonic character, practicality and minimal rationality. 2) The path taken by Avicenna in his book "Al-Isharat wal-tanbihat (Remarks and Admonitions)", which leads from logic to mysticism, can be continued in his ethical theory metaphorically and certainly through a relatively free reading. In the sense that a person's ethical choice begins with the motive of fulfilling biological needs and human interactions, but the correspondence of an ethical action with nature and the rhythm of life accelerates the continuation of ethical choice and finally interprets a mystical life with a meaning that corresponds to the psychological-evolutionary descriptions of mysticism.